An approach to Repertorio Americano (1919-1958) - González Zuñiga, Julián (2018)
Repertorio Americano is a well-known Spanish American journal published in Costa Rica from 1919 to 1958 by Joaquín García Monge-writer, journalist, and scholar-. This cultural enterprise was a guest influence for intellectuals from different countries.